Analisis Kestabilan Lereng Pit B Tambang PT. Miyor Pratama Coal, Desa Kumanis Atas Kec. Talawi, Sawahlunto Sumatera Barat - Refky Adi Nata; Alexander Alexander (Jurusan Teknik Pertambangan, Fakultas Teknik, Universitas Bangka Belitung, 2019)
The purpose of this research is a classification of rock from slopes and analyzes safety factor of slope by fellenius and janbu method. This type of research classified as descriptive. For class of rock mass based on bieniawski 1989 and for processing helped with software slide v. 6.0. Research results explain the total weights of Rock Mass Rating (RMR) from the results of the data from field, the total weights is = 46 so the rocks are at class III (moderate), with cohesion value 250 kPa and the friction angle is 30 o. The value of the slope safety factor pit B PT. Miyor Pratama Coal after using the slide programme V. 6.0 with method of Bishop has Safety factor = 2,093, and with Janbu method has safety factor = 2,180. From two methods include safe condition > 1.